2016
DOI: 10.1371/journal.pone.0167008
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Contributors to Rhythm Outcome of Atrial Fibrillation Catheter Ablation – Pathway Enrichment Analysis of GWAS Data

Abstract: BackgroundLeft atrial enlargement and persistent atrial fibrillation (AF) are well-known predictors for arrhythmia recurrence after AF catheter ablation (LRAF). In this study, by using pathway enrichment analysis of GWAS data, we tested the hypothesis that genetic pathways associated with these phenotypes are also associated with LRAF.MethodsSamples from 660 patients with paroxysmal (n = 370) or persistent AF (n = 290) undergoing de-novo AF catheter ablation were genotyped for ~1,000,000 SNPs. SNPs found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…This study was based on recently published findings ( Husser et al, 2016a ). Patient characteristics, clinical parameters, genome-wide association analysis, gene-based association testing, pathway analysis, and gene lists can be found in Supplementary Methods and Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was based on recently published findings ( Husser et al, 2016a ). Patient characteristics, clinical parameters, genome-wide association analysis, gene-based association testing, pathway analysis, and gene lists can be found in Supplementary Methods and Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Common genetic variants contribute to the progression and recurrence of atrial fibrillation (AF; Olesen et al, 2014 ). We recently used genome-wide association study data from 660 AF patients to detect common variants that associate with left atrial diameter, AF type (paroxysmal vs. persistent AF), and AF recurrence ( Husser et al, 2016a , b ). Based on the hypothesis that all genetic variants irrespective of their significance level contribute to genetic background, we included all variants with p < 0.05 in our analysis irrespective if they were coding, non-coding, synonymous, or non-synonymous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study extends the concept of analyzing clinically-overlapping phenotypes with shared genotypes. By applying this, we were already able to identify genes of calcium signaling pathway ( SLC8A1 ) and the ECM receptor interaction pathway ( ITGA9 ) to associate with recurring AF (Husser et al, 2016a ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Husser's group performed clinical and genetic predictor analysis based on pathway enrichment analysis of GWAS (Genome-wide Association Study) data, and demonstrated that the ECM-receptor interaction pathways were significantly associated with left atrial enlargement and AF type and response to AF catheter ablation [33]. Presumably, ECM remodeling revealed complex relationships between cell-to-cell interactions and communication, and was validated as a central mediator that tightly links ion channels with the development of an ectopic pacemaker [33]. Although the previous studies and our results have provided evidence to show that ECM interaction is a potential target, the precise molecular mechanisms of the ECM in the progressive nature of AF are still unknown.…”
Section: Col6a6mentioning
confidence: 99%